Structurally controllable hollow carbon spheres for gaseous benzene adsorption. Issue 1 (February 2023) - Chen, Guanyu; Yang, Xiaobing; Ma, Yuansheng; Ruan, Chichi; Chen, Qilin; Jin, Xin; Sun, Junwei; He, Song
Abstract: Hollow carbon spheres (HCSs) with controllable morphology, stable physicochemical properties, high surface area, and large pore volume achieved without any acidic or alkaline activators, are likely to be an attractive adsorption material. Nevertheless, reports on applying HCSs for adsorption separation are relatively limited, especially for volatile organic compounds (VOCs). Herein, a series of HCSs were successfully synthesized by a simple one-pot, surfactant-free method and varying ethanol/water volume ratios, compositions of silicon alkoxides (tetrapropyl orthosilicate/tetraethyl orthosilicate, TPOS/TEOS), lag time for adding resorcinol-formaldehyde (RF) resin precursors, and system temperatures. The differences between these HCSs in terms of average particle size, internal cavity diameter, shell thickness, specific surface area, and porosity were well elucidated. HCS-11 synthesized at 10 °C had the most desirable specific surface area (2531.29 m 2 g −1 ) and total pore volume (3.527 cm 3 g −1 ) in this study, which was superior to many HCSs in the literature, and therefore was selected for subsequent benzene adsorption/desorption tests. As expected, HCS-11 exhibited a static benzene adsorption capacity of up to 21.363 mmol g −1 at 293 K. In addition, the effects of different initial concentrations, gas flow rates, and ambient temperatures on dynamic benzene adsorption by HCS-11 were systematically investigated. The high adsorption capacity of HCS-11 remained stable after six consecutive adsorption-desorption cycles, indicating its good thermal regeneration capability. The excellent porosity, high cyclic adsorption capacity, and rapid desorption kinetics of HCS-11 made it promising for VOC abatement. Graphical Abstract: ga1 Highlights: ● The effects of 4 types of synthesis parameters on HCSs' morphology and porosity were elaborated. ● HCS-11 prepared at 10 °C had an outstanding specific surface area and pore volume. ● The static benzene adsorption capacity of HCS-11 was up to 21.363 mmol g −1 at 293 K. ● The effects of different environmental parameters on dynamic benzene adsorption by HCS-11 were studied. ● HCS-11 exhibited rapid desorption kinetics at a relatively low temperature.